Paper pulp / polyethylene composite material and preparation method thereof

By using modified polyethylene and modified pulp preparation methods, combined with flame retardant light stabilizers and laccase mediator systems, the interfacial compatibility and durability issues of pulp/polyethylene composite materials were solved, achieving improvements in high strength, water resistance, moisture resistance, weather resistance, and flame retardancy.

CN120865667APending Publication Date: 2025-10-31深圳市隆发新材料技术有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510956300.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-11
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Existing pulp/polyethylene composite materials are difficult to mix evenly during the mixing process, resulting in poor interfacial compatibility, low interfacial bonding strength, poor high temperature and UV resistance, insufficient flame retardancy, and poor water and moisture resistance.

Method used

The preparation method of modified polyethylene and modified pulp involves enzymatic modification of the pulp by maleic anhydride modification and the addition of flame retardant light stabilizers and ultraviolet absorbers, combined with a laccase mediator system to enhance interfacial compatibility and mechanical properties, and then forming a composite material by extrusion granulation.

Benefits of technology

It improves the interfacial bonding strength and mechanical properties of pulp/polyethylene composites, enhances water and moisture resistance, and improves flame retardancy, weather resistance, temperature resistance, and UV resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005494587670000021
    Figure BDA0005494587670000021
  • Figure BDA0005494587670000031
    Figure BDA0005494587670000031
  • Figure BDA0005494587670000061
    Figure BDA0005494587670000061
Patent Text Reader

Abstract

The invention provides a paper pulp / polyethylene composite material and a preparation method thereof, and belongs to the technical field of composite materials. Comprising the following raw materials in parts by weight: 30-50 parts of modified polyethylene, 25-45 parts of modified paper pulp, 2-4 parts of polyethylene wax, 1-2 parts of graphene oxide, 0.5-1.5 parts of glass fibers, 0.3-0.5 part of sodium citrate, 1-2 parts of ethylene bisstearamide, 2-3 parts of gelatin and 4-7 parts of deionized water. The paper pulp / polyethylene composite material prepared by the preparation method disclosed by the invention has the advantages of obviously improved interface bonding strength, better mechanical property, excellent water resistance and moisture resistance, improved flame retardance, weather resistance, temperature resistance and ultraviolet resistance, and wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite materials technology, specifically to a pulp / polyethylene composite material and its preparation method. Background Technology

[0002] Pulp / polyethylene composite material is a new type of composite material that has emerged rapidly in recent years both domestically and internationally. It is a new material made by mixing polyethylene and pulp. It has good waterproof and moisture-proof properties and excellent environmental performance, and is widely used in building materials, furniture and other industries.

[0003] However, in the preparation of pulp / polyethylene composites, existing technologies encounter difficulties in achieving uniform mixing due to the significant density difference between the dried pulp and polyethylene resin. Furthermore, pulp contains a large amount of cellulose and numerous polar groups such as hydroxyl groups, making it hydrophilic; while polyethylene is a non-polar polymer and hydrophobic. This polarity difference leads to poor interfacial compatibility, hindering the formation of a good bond.

[0004] Moreover, the pulp / polyethylene composite materials produced by existing technologies have poor high temperature resistance and UV resistance. After being exposed to high temperature or UV radiation, their strength properties are greatly reduced, which seriously affects their performance. In addition, their flame retardancy is poor.

[0005] In addition, composite materials have poor water and moisture resistance. Pulp fibers are hydrophilic and easily absorb moisture, while polyethylene is hydrophobic. This difference in polarity makes the composite material prone to interfacial debonding in humid environments, reducing its mechanical properties and durability.

[0006] Therefore, providing a pulp / polyethylene composite material and its preparation method to avoid agglomeration during the mixing process, enhance the strength properties of the composite material, and ensure minimal loss of strength properties after high temperature or ultraviolet irradiation are technical problems that urgently need to be solved in the prior art. Summary of the Invention

[0007] The purpose of this invention is to propose a pulp / polyethylene composite material and its preparation method, which significantly improves the interfacial bonding strength, has good mechanical properties, excellent water and moisture resistance, and improves flame retardancy, weather resistance, temperature resistance, and UV resistance, and has broad application prospects.

[0008] The technical solution of this invention is implemented as follows:

[0009] This invention provides a pulp / polyethylene composite material comprising the following raw materials in parts by weight: 30-50 parts modified polyethylene, 25-45 parts modified pulp, 2-4 parts polyethylene wax, 1-2 parts graphene oxide, 0.5-1.5 parts glass fiber, 0.3-0.5 parts sodium citrate, 1-2 parts ethylene bis-stearamide, 2-3 parts gelatin, and 4-7 parts deionized water.

[0010] As a further improvement of the present invention, the method for preparing the modified polyethylene is as follows:

[0011] S1. Polyethylene and maleic anhydride are mixed and added to a mixer, melt-blended, extruded, and granulated to obtain maleic anhydride-modified polyethylene;

[0012] S2. The flame-retardant light stabilizer, flame-retardant ultraviolet absorber, maleic anhydride modified polyethylene and p-toluenesulfonic acid are mixed and added to a mixer, melt-blended, extruded, and granulated to obtain modified polyethylene.

[0013] As a further improvement of the present invention, in step S1, the mass ratio of polyethylene to maleic anhydride is 90-100:5-10, the melt blending temperature is 155-165℃, the rotation speed is 20-50 r / min, and the time is 2-5 min; in step S2, the mass ratio of flame retardant light stabilizer, flame retardant ultraviolet absorber, maleic anhydride modified polyethylene, and p-toluenesulfonic acid is 3-5:2-4:15-25:0.1-0.2, the melt blending temperature is 155-165℃, the rotation speed is 200-500 r / min, and the time is 3-5 h.

[0014] As a further improvement of the present invention, the structural formula of the flame retardant light stabilizer is shown in Formula I:

[0015]

[0016] The preparation method is as follows:

[0017] 2-hydroxybenzophenone, melamine, and formaldehyde solution were added to ethylene glycol diethyl ether, heated and stirred to react, filtered, washed, and dried to obtain a flame-retardant light stabilizer.

[0018] As a further improvement of the present invention, the molar ratio of 2-hydroxybenzophenone, melamine and formaldehyde is 3-3.1:1:3.2-4, and the heating and stirring reaction temperature is 90-100℃, and the time is 20-24h.

[0019] As a further improvement of the present invention, the structural formula of the flame-retardant ultraviolet absorber is shown in Formula II:

[0020]

[0021] The preparation method is as follows:

[0022] A flame-retardant ultraviolet absorber was prepared by adding 2-(2-hydroxy-5-methylphenyl)benzotriazole, melamine, and formaldehyde solution to ethylene glycol diethyl ether, heating and stirring the mixture, filtering, washing, and drying.

[0023] As a further improvement of the present invention, the molar ratio of 2-(2-hydroxy-5-methylphenyl)benzotriazole, melamine and formaldehyde is 3-3.1:1:3.2-4, and the heating and stirring reaction temperature is 95-105℃, and the time is 20-24h.

[0024] As a further improvement of the present invention, the method for preparing the modified pulp is as follows:

[0025] T1. Mix laccase, hydrogen peroxide and ferrous salt into PBS buffer, stir and mix well to prepare laccase / Fenton mediator system;

[0026] T2. Add laccase / Fenton mediator system to pulp, carry out enzymatic hydrolysis, add ethanol, filter, wash with solids, dry, and obtain enzymatically hydrolyzed pulp;

[0027] T3. Add the enzymatically hydrolyzed pulp to N,N-dimethylformamide, add p-toluenesulfonic acid, oleic acid and cinnamic acid, heat and stir to react, add water to precipitate, filter, wash and dry to obtain modified pulp.

[0028] As a further improvement of the present invention, in step T1, the mass ratio of laccase, hydrogen peroxide and ferrous salt is 1-1.5:15-20:1-2, the ferrous salt is ferrous chloride or ferrous sulfate, and the pH value of the PBS buffer is 3-4; in step T2, the mass ratio of pulp and laccase / Fenton mediator system is 10-12:50-70, the temperature of the enzymatic hydrolysis reaction is 30-34℃, the time is 30-60 min, and the pulp is unbleached poplar chemothermal mechanical pulp with a freeness of 40-50°SR; in step T3, the mass ratio of enzymatically hydrolyzed pulp, p-toluenesulfonic acid, oleic acid and cinnamic acid is 10-15:0.5-1:3-5:2-4, the temperature of the heating and stirring reaction is 100-110℃, and the time is 4-6 h.

[0029] This invention further protects a method for preparing the above-mentioned pulp / polyethylene composite material, comprising the following steps: mixing modified polyethylene, modified pulp, polyethylene wax, graphene oxide, glass fiber, sodium citrate, ethylene bis-stearamide, gelatin and deionized water evenly, drying to obtain a mixture, adding it to a twin-screw extruder for extrusion granulation to obtain granules, with a die head temperature of 175-185℃, and feeding the granules into an extruder for extrusion molding to obtain the pulp / polyethylene composite material.

[0030] The present invention has the following beneficial effects:

[0031] This invention prepares a flame-retardant light stabilizer and a flame-retardant ultraviolet absorber. Using melamine as the core, polybenzophenone and polybenzotriazole structures are synthesized. The preparation method is simple and the conditions are mild. The obtained products have good light stability, ultraviolet absorption performance and flame retardancy. They are also safe, non-toxic, soluble and thermally stable. Due to the presence of hydroxyl structures, they can also undergo esterification reaction with maleic anhydride-grafted modified polyethylene for coupling. This allows the flame-retardant light stabilizer and flame-retardant ultraviolet absorber to be uniformly dispersed in polyethylene resin, improving flame retardancy, weather resistance and temperature resistance, while the mechanical properties are not affected.

[0032] This invention employs a laccase-mediated system to modify pulp. Laccase is a lignin-degrading enzyme and a ketone-containing polyphenol oxidase. In the presence of certain electron-transferring mediators and oxygen, it can catalytically oxidize phenols, aromatic compounds, and aliphatic amines. Laccase can oxidize hydrogen peroxide and the Fenton system of ferrous ions, giving these small molecule compounds a certain degree of stability and a high redox potential. These small molecule compounds are called mediators, and the system in which they act with laccase is called a laccase-mediated system. Fenton mediators can generate highly oxidizing hydroxyl radicals, whose oxidation energy... The reaction is stronger than either laccase or Fenton reaction alone, and can more effectively degrade large organic molecules such as lignin, causing the structure of lignin to break and decompose, accelerating the reaction rate and improving the overall reaction efficiency of the laccase-Fenton system. In addition, while oxidizing lignin, the Fenton mediator has a certain protective effect on cellulose, which can prevent cellulose from being subjected to excessive oxidative damage during the reaction, and helps to maintain the integrity and strength of cellulose, thereby improving the pulp properties, improving the mechanical and hydrophobic properties of the pulp, improving the compatibility with modified polyethylene, and improving the brightness of the pulp.

[0033] In addition, the enzymatic hydrolysis of pulp is further esterified with oleic acid and cinnamic acid, which improves the antibacterial and hydrophobic properties of the pulp and introduces double bonds, which can further improve the compatibility of pulp with modified polyethylene resin. This improves the water resistance, moisture resistance and mechanical properties of the prepared pulp / polyethylene composite material, and significantly improves the interfacial bonding strength.

[0034] The pulp / polyethylene composite material prepared by this invention has significantly improved interfacial bonding strength, good mechanical properties, excellent water and moisture resistance, and improved flame retardancy, weather resistance, temperature resistance, and UV resistance, and has broad application prospects. Detailed Implementation

[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0036] Laccase, >0.5 U / mg; pulp: unbleached poplar chemothermomechanical pulp, freeness 45°SR; graphene oxide, purity >95%, thickness 3.5-8 nm, number of layers 5-10, specific surface area 200-300 m² / g. 2 / g.

[0037] Preparation Example 1: Preparation of Flame Retardant Light Stabilizer

[0038] Synthesis route:

[0039]

[0040] The method is as follows:

[0041] 0.3 mol 2-hydroxybenzophenone, 0.1 mol melamine, and 50 mL of an aqueous solution containing 0.32 mol formaldehyde were added to 150 mL of ethylene glycol diethyl ether. The mixture was heated to 95 °C and stirred for 24 h. After filtration, washing, and drying, a flame-retardant light stabilizer was obtained with a yield of 80%. ESI-MS calculated value: C 45 H 37 N6O6(M+H) + 757.27, measured value: 757.3.

[0042] MRI results: 1 H NMR (300MHz, CDCl3) δ7.7-7.72 (m, 6H), 7.35-7.45 (m, 12H), 7.05-7.09 (m, 3H), 6.8-6.85 (m, 3H), 5.0 (br, 3H), 4.35 (s, 6H), 4.2 (br, 3H).

[0043] Preparation Example 2: Preparation of Flame-Retardant Ultraviolet Absorber

[0044] Synthesis route:

[0045]

[0046] The method is as follows:

[0047] 0.3 mol of 2-(2-hydroxy-5-methylphenyl)benzotriazole, 0.1 mol of melamine, and 50 mL of an aqueous solution containing 0.35 mol of formaldehyde were added to 150 mL of ethylene glycol diethyl ether. The mixture was heated to 100 °C and stirred for 22 h. After filtration, washing, and drying, a flame-retardant light stabilizer was obtained with a yield of 82%. ESI-MS calculated value: C 45 H 40 N 15 O3(M+H) + 838.34, measured value: 838.3.

[0048] MRI results: 1 H NMR (300MHz, CDCl3) δ6.65-6.72(m, 12H), 6.15-6.2(m, 6H), 5.1(br, 3H), 4.27(s, 6H), 3.8(br, 3H), 2.32(s, 9H).

[0049] Preparation Example 3: Preparation of Modified Polyethylene

[0050] The method is as follows:

[0051] S1. Polyethylene and maleic anhydride are mixed in a mass ratio of 90:5 and added to a mixer for melt blending at a temperature of 155℃, a rotation speed of 20r / min, and a time of 2min. The mixture is then extruded and granulated to obtain maleic anhydride modified polyethylene.

[0052] S2. The flame-retardant light stabilizer prepared in Preparation Example 1, the flame-retardant ultraviolet absorber prepared in Preparation Example 2, maleic anhydride modified polyethylene and p-toluenesulfonic acid were mixed in a mass ratio of 3:2:15:0.1 and added to a mixer for melt blending at a temperature of 155°C, a rotation speed of 200 r / min and a time of 5 h. The mixture was then extruded and granulated to obtain modified polyethylene.

[0053] Preparation Example 4: Preparation of Modified Polyethylene

[0054] The method is as follows:

[0055] S1. Polyethylene and maleic anhydride are mixed in a mass ratio of 100:10 and added to a mixer for melt blending at a temperature of 165℃, a rotation speed of 50r / min, and a time of 5min. The mixture is then extruded and granulated to obtain maleic anhydride modified polyethylene.

[0056] S2. The flame-retardant light stabilizer prepared in Preparation Example 1, the flame-retardant ultraviolet absorber prepared in Preparation Example 2, maleic anhydride modified polyethylene and p-toluenesulfonic acid were mixed in a mass ratio of 5:4:25:0.2 and added to a mixer for melt blending at a temperature of 165°C, a rotation speed of 200 r / min and a time of 5 h. The mixture was then extruded and granulated to obtain modified polyethylene.

[0057] Preparation Example 5: Preparation of Modified Polyethylene

[0058] The method is as follows:

[0059] S1. Polyethylene and maleic anhydride are mixed in a mass ratio of 95:7 and added to a mixer for melt blending at a temperature of 160℃, a rotation speed of 30r / min, and a time of 3min. The mixture is then extruded and granulated to obtain maleic anhydride modified polyethylene.

[0060] S2. The flame-retardant light stabilizer prepared in Preparation Example 1, the flame-retardant ultraviolet absorber prepared in Preparation Example 2, maleic anhydride modified polyethylene and p-toluenesulfonic acid were mixed in a mass ratio of 4:3:20:0.15 and added to a mixer for melt blending at a temperature of 160°C, a rotation speed of 350 r / min and a time of 4 h. The mixture was then extruded and granulated to obtain modified polyethylene.

[0061] Comparative Preparation Example 1

[0062] The difference from Preparation Example 5 is that no flame retardant light stabilizer was added in step S2.

[0063] Specifically as follows:

[0064] S2. The flame-retardant ultraviolet absorber obtained in Preparation Example 2, maleic anhydride modified polyethylene and p-toluenesulfonic acid were mixed in a mass ratio of 4:3:20:0.15 and added to a mixer for melt blending at a temperature of 160°C, a rotation speed of 350 r / min and a time of 4 h. The mixture was then extruded and granulated to obtain modified polyethylene.

[0065] Comparative Preparation Example 2

[0066] The difference from Preparation Example 5 is that no flame-retardant ultraviolet absorber was added in step S2.

[0067] Specifically as follows:

[0068] S2. The flame retardant light stabilizer obtained in Preparation Example 1, maleic anhydride modified polyethylene and p-toluenesulfonic acid were mixed in a mass ratio of 7:20:0.15 and added to a mixer for melt blending at a temperature of 160°C, a rotation speed of 350 r / min and a time of 4 h. The mixture was then extruded and granulated to obtain modified polyethylene.

[0069] Comparative preparation example 3

[0070] The difference from preparation example 5 is that step S2 was not performed.

[0071] Specifically as follows:

[0072] Polyethylene and maleic anhydride were mixed in a mass ratio of 95:7 and added to a mixer for melt blending at a temperature of 160℃, a rotation speed of 30 r / min, and a time of 3 min. The mixture was then extruded and granulated to obtain modified polyethylene.

[0073] Preparation Example 6: Preparation of Modified Pulp

[0074] The method is as follows:

[0075] T1. Mix 1g laccase, 15g hydrogen peroxide and 1g ferrous chloride into 100mL of PBS buffer with pH 3, stir and mix for 30min to obtain the laccase / Fenton mediator system.

[0076] T2. Add 50g of laccase / Fenton mediator system to 10g of pulp, enzymatically hydrolyze at 30℃ for 30min, add an equal volume of ethanol, filter, wash the solid, dry, and obtain enzymatically hydrolyzed pulp.

[0077] T3. Add 10g of enzymatically hydrolyzed pulp to 300mL of N,N-dimethylformamide, add 0.5g of p-toluenesulfonic acid, add 3g of oleic acid and 2g of cinnamic acid, heat to 100℃, stir and react for 4h, add an equal volume of water, precipitate, filter, wash, and dry to obtain modified pulp.

[0078] Preparation Example 7: Preparation of Modified Pulp

[0079] The method is as follows:

[0080] T1. Mix 1.5g laccase, 20g hydrogen peroxide and 2g ferrous sulfate into 100mL of PBS buffer with pH 4 and stir for 30min to prepare the laccase / Fenton mediator system.

[0081] T2. Add 70g of laccase / Fenton mediator system to 12g of pulp, enzymatically hydrolyze at 34℃ for 30-60min, add an equal volume of ethanol, filter, wash the solid, dry, and obtain enzymatically hydrolyzed pulp.

[0082] T3. Add 15g of enzymatically hydrolyzed pulp to 300mL of N,N-dimethylformamide, add 1g of p-toluenesulfonic acid, 5g of oleic acid and 4g of cinnamic acid, heat to 110℃, stir and react for 6h, add an equal volume of water, precipitate, filter, wash and dry to obtain modified pulp.

[0083] Preparation Example 8: Preparation of Modified Pulp

[0084] The method is as follows:

[0085] T1. Mix 1.2g laccase, 17g hydrogen peroxide and 1.5g ferrous chloride into 100mL of PBS buffer with a pH of 3.5 and stir for 30min to obtain the laccase / Fenton mediator system.

[0086] T2. Add 60g of laccase / Fenton mediator system to 11g of pulp, enzymatically hydrolyze at 32℃ for 45min, add an equal volume of ethanol, filter, wash the solid, dry, and obtain enzymatically hydrolyzed pulp.

[0087] T3. Add 12g of enzymatically hydrolyzed pulp to 300mL of N,N-dimethylformamide, add 0.7g of p-toluenesulfonic acid, add 4g of oleic acid and 3g of cinnamic acid, heat to 105℃, stir and react for 5h, add an equal volume of water, precipitate, filter, wash, and dry to obtain modified pulp.

[0088] Comparative preparation example 4

[0089] The difference from Preparation Example 8 is that ferrous chloride was not added in step T1.

[0090] Specifically as follows:

[0091] T1. Mix 1.2g laccase and 18.5g hydrogen peroxide and add them to 100mL of PBS buffer with a pH of 3.5. Stir and mix for 30min to obtain the laccase / H2O2 mediator system.

[0092] Comparative preparation example 5

[0093] The difference from Preparation Example 8 is that oleic acid was not added in step T3.

[0094] Specifically as follows:

[0095] T3. Add 12g of enzymatically hydrolyzed pulp to 300mL of N,N-dimethylformamide, add 0.7g of p-toluenesulfonic acid and 7g of cinnamic acid, heat to 105℃, stir and react for 5h, add an equal volume of water, precipitate, filter, wash, and dry to obtain modified pulp.

[0096] Comparative preparation example 6

[0097] The difference from Preparation Example 8 is that cinnamic acid was not added in step T3.

[0098] Specifically as follows:

[0099] T3. Add 12g of enzymatically hydrolyzed pulp to 300mL of N,N-dimethylformamide, add 0.7g of p-toluenesulfonic acid and 7g of oleic acid, heat to 105℃, stir and react for 5h, add an equal volume of water, precipitate, filter, wash, and dry to obtain modified pulp.

[0100] Comparative preparation example 7

[0101] The difference from preparation example 8 is that step T3 was not performed.

[0102] Specifically as follows:

[0103] T1. Mix 1.2g laccase, 17g hydrogen peroxide and 1.5g ferrous chloride into 100mL of PBS buffer with a pH of 3.5 and stir for 30min to obtain the laccase / Fenton mediator system.

[0104] T2. Add 60g of laccase / Fenton mediator system to 11g of pulp, enzymatically hydrolyze at 32℃ for 45min, add an equal volume of ethanol, filter, wash the solid, and dry to obtain modified pulp.

[0105] Example 1

[0106] This embodiment provides a pulp / polyethylene composite material.

[0107] Raw material composition (parts by weight): 30 parts of modified polyethylene obtained in Preparation Example 3, 25 parts of modified pulp obtained in Preparation Example 6, 2 parts of polyethylene wax, 1 part of graphene oxide, 0.5 parts of glass fiber, 0.3 parts of sodium citrate, 1 part of ethylene bis-stearamide, 2 parts of gelatin, and 4 parts of deionized water.

[0108] The preparation method includes the following steps: mixing modified polyethylene, modified pulp, polyethylene wax, graphene oxide, glass fiber, sodium citrate, ethylene bis-stearamide, gelatin and deionized water evenly, drying to obtain a mixture, adding it to a twin-screw extruder for extrusion granulation to obtain granules, with the die head temperature at 175℃, and feeding the granules into the extruder for extrusion molding to obtain pulp / polyethylene composite material.

[0109] Example 2

[0110] This embodiment provides a pulp / polyethylene composite material.

[0111] Raw material composition (parts by weight): 50 parts of modified polyethylene obtained in Preparation Example 4, 45 parts of modified pulp obtained in Preparation Example 7, 4 parts of polyethylene wax, 2 parts of graphene oxide, 1.5 parts of glass fiber, 0.5 parts of sodium citrate, 2 parts of ethylene bis-stearamide, 3 parts of gelatin, and 7 parts of deionized water.

[0112] The preparation method includes the following steps: mixing modified polyethylene, modified pulp, polyethylene wax, graphene oxide, glass fiber, sodium citrate, ethylene bis-stearamide, gelatin and deionized water evenly, drying to obtain a mixture, adding it to a twin-screw extruder for extrusion granulation to obtain granules, with the die head temperature at 185℃, and feeding the granules into the extruder for extrusion molding to obtain pulp / polyethylene composite material.

[0113] Example 3

[0114] This embodiment provides a pulp / polyethylene composite material.

[0115] Raw material composition (parts by weight): 40 parts of modified polyethylene obtained in Preparation Example 5, 35 parts of modified pulp obtained in Preparation Example 8, 3 parts of polyethylene wax, 1.5 parts of graphene oxide, 1 part of glass fiber, 0.4 parts of sodium citrate, 1.5 parts of ethylene bis-stearamide, 2.5 parts of gelatin, and 5.5 parts of deionized water.

[0116] The preparation method includes the following steps: mixing modified polyethylene, modified pulp, polyethylene wax, graphene oxide, glass fiber, sodium citrate, ethylene bis-stearamide, gelatin and deionized water evenly, drying to obtain a mixture, adding it to a twin-screw extruder for extrusion granulation to obtain granules, with the die head temperature at 180℃, and feeding the granules into the extruder for extrusion molding to obtain pulp / polyethylene composite material.

[0117] Comparative Example 1

[0118] The difference from Example 3 is that the modified polyethylene was prepared by Comparative Preparation Example 1.

[0119] Comparative Example 2

[0120] The difference from Example 3 is that the modified polyethylene was prepared from Comparative Preparation Example 2.

[0121] Comparative Example 3

[0122] The difference from Example 3 is that the modified polyethylene was prepared by Comparative Preparation Example 3.

[0123] Comparative Example 4

[0124] The difference from Example 3 is that the modified pulp was prepared from Comparative Preparation Example 4.

[0125] Comparative Example 5

[0126] The difference from Example 3 is that the modified pulp was prepared from Comparative Preparation Example 5.

[0127] Comparative Example 6

[0128] The difference from Example 3 is that the modified pulp was prepared from Comparative Preparation Example 6.

[0129] Comparative Example 7

[0130] The difference from Example 3 is that the modified pulp was prepared from Comparative Preparation Example 7.

[0131] Comparative Example 8

[0132] The difference from Example 3 is that the modified polyethylene is replaced by polyethylene of equal mass.

[0133] Comparative Example 9

[0134] The difference from Example 3 is that the modified pulp is replaced with paper pulp.

[0135] Test Example 1 Mechanical Property Test

[0136] The mechanical properties of the pulp / polyethylene composite materials prepared in Examples 1-3 and Comparative Examples 1-9 were tested. The results are shown in Table 1.

[0137] Tensile strength was tested according to GB / T 1040.2-2022 standard;

[0138] Bending strength was tested according to GB / T 9341-2008 standard;

[0139] Impact strength was tested in accordance with GB / T 1843-2008 standard.

[0140] Table 1

[0141]

[0142]

[0143] As can be seen from the table above, the pulp / polyethylene composite materials prepared in Examples 1-3 of the present invention have good mechanical properties.

[0144] Test Example 2

[0145] The pulp / polyethylene composite materials prepared in Examples 1-3 and Comparative Examples 1-9 were placed in a high-temperature environment (52°C, 80% humidity for 15 days), a humid environment (95% humidity for 15 days), and an ultraviolet irradiation environment (1800W high-pressure mercury lamp for 15 days, ultraviolet light wavelength of 380nm) for treatment, respectively. The tensile strength of the materials was tested and the tensile strength retention rate was calculated. The results are shown in Table 2.

[0146] Table 2

[0147]

[0148] As can be seen from the table above, the pulp / polyethylene composite materials prepared in Examples 1-3 of the present invention have good high temperature resistance, moisture resistance, and UV resistance.

[0149] Test Example 3

[0150] The pulp / polyethylene composite materials prepared in Examples 1-3 and Comparative Examples 1-9 were subjected to performance tests.

[0151] The antibacterial and antifungal properties were tested according to the national standard GB 21551.2-2010.

[0152] The vertical limiting oxygen index (LOI) was tested according to GB / T 2406.2-2009, with sample dimensions of 80mm×10mm×4mm.

[0153] The results are shown in Table 3.

[0154] Table 3

[0155] Group Antibacterial rate (%) (E. coli) Anti-mildew rating LOI (%) Example 1 >99 0 28.9 Example 2 >99 0 29.2 Example 3 >99 0 29.9 Comparative Example 1 97.8 0 28.4 Comparative Example 2 98.2 0 28.1 Comparative Example 3 92.5 1 23.2 Comparative Example 4 97.8 0 28.3 Comparative Example 5 96.9 1 28.0 Comparative Example 6 92.1 1 27.4 Comparative Example 7 89.8 2 27.0 Comparative Example 8 88.7 2 21.1 Comparative Example 9 86.2 2 27.5

[0156] As shown in the table above, the pulp / polyethylene composite materials prepared in Examples 1-3 of this invention have good flame retardant and antibacterial and mildew-proof properties.

[0157] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A pulp / polyethylene composite material, characterized in that, The raw materials include the following parts by weight: 30-50 parts modified polyethylene, 25-45 parts modified pulp, 2-4 parts polyethylene wax, 1-2 parts graphene oxide, 0.5-1.5 parts glass fiber, 0.3-0.5 parts sodium citrate, 1-2 parts ethylene bis-stearamide, 2-3 parts gelatin, and 4-7 parts deionized water.

2. The pulp / polyethylene composite material according to claim 1, characterized in that, The modified polyethylene is prepared as follows: S1. Polyethylene and maleic anhydride are mixed and added to a mixer, melt-blended, extruded, and granulated to obtain maleic anhydride-modified polyethylene; S2. The flame retardant light stabilizer, flame retardant ultraviolet absorber, maleic anhydride modified polyethylene and p-toluenesulfonic acid are mixed and added to a mixer, melt-blended, extruded, and granulated to obtain modified polyethylene.

3. The pulp / polyethylene composite material according to claim 2, characterized in that, In step S1, the mass ratio of polyethylene to maleic anhydride is 90-100:5-10, the melt blending temperature is 155-165℃, the rotation speed is 20-50 r / min, and the time is 2-5 min; in step S2, the mass ratio of flame retardant light stabilizer, flame retardant ultraviolet absorber, maleic anhydride modified polyethylene, and p-toluenesulfonic acid is 3-5:2-4:15-25:0.1-0.2, the melt blending temperature is 155-165℃, the rotation speed is 200-500 r / min, and the time is 3-5 h.

4. The pulp / polyethylene composite material according to claim 2, characterized in that, The structural formula of the flame-retardant light stabilizer is shown in Formula I: The preparation method is as follows: 2-hydroxybenzophenone, melamine, and formaldehyde solution were added to ethylene glycol diethyl ether, heated and stirred to react, filtered, washed, and dried to obtain a flame-retardant light stabilizer.

5. The pulp / polyethylene composite material according to claim 4, characterized in that, The molar ratio of 2-hydroxybenzophenone, melamine, and formaldehyde is 3-3.1:1:3.2-4, and the heating and stirring reaction is carried out at a temperature of 90-100℃ for 20-24 hours.

6. The pulp / polyethylene composite material according to claim 2, characterized in that, The structural formula of the flame-retardant ultraviolet absorber is shown in Formula II: The preparation method is as follows: A flame-retardant ultraviolet absorber was prepared by adding 2-(2-hydroxy-5-methylphenyl)benzotriazole, melamine, and formaldehyde solution to ethylene glycol diethyl ether, heating and stirring the mixture, filtering, washing, and drying.

7. The pulp / polyethylene composite material according to claim 6, characterized in that, The molar ratio of 2-(2-hydroxy-5-methylphenyl)benzotriazole, melamine, and formaldehyde is 3-3.1:1:3.2-4, and the heating and stirring reaction is carried out at a temperature of 95-105℃ for 20-24 hours.

8. The pulp / polyethylene composite material according to claim 1, characterized in that, The modified pulp is prepared as follows: T1. Mix laccase, hydrogen peroxide and ferrous salt into PBS buffer, stir and mix well to prepare laccase / Fenton mediator system; T2. Add laccase / Fenton mediator system to pulp, carry out enzymatic hydrolysis, add ethanol, filter, wash with solids, dry, and obtain enzymatically hydrolyzed pulp; T3. Add the enzymatically hydrolyzed pulp to N,N-dimethylformamide, add p-toluenesulfonic acid, oleic acid and cinnamic acid, heat and stir to react, add water to precipitate, filter, wash and dry to obtain modified pulp.

9. The pulp / polyethylene composite material according to claim 8, characterized in that, In step T1, the mass ratio of laccase, hydrogen peroxide, and ferrous salt is 1-1.5:15-20:1-2, and the ferrous salt is ferrous chloride or ferrous sulfate. The pH of the PBS buffer is 3-4. In step T2, the mass ratio of pulp and laccase / Fenton mediator system is 10-12:50-70. The enzymatic hydrolysis reaction temperature is 30-34℃, and the time is 30-60 min. The pulp is unbleached poplar chemothermal mechanical pulp with a freeness of 40-50°SR. In step T3, the mass ratio of enzymatically hydrolyzed pulp, p-toluenesulfonic acid, oleic acid, and cinnamic acid is 10-15:0.5-1:3-5:2-4. The heating and stirring reaction temperature is 100-110℃, and the time is 4-6 h.

10. A method for preparing a pulp / polyethylene composite material as described in any one of claims 1-9, characterized in that, The process includes the following steps: mixing modified polyethylene, modified pulp, polyethylene wax, graphene oxide, glass fiber, sodium citrate, ethylene bis-stearamide, gelatin and deionized water evenly, drying to obtain a mixture, adding it to a twin-screw extruder for granulation to obtain granules, with the die head temperature at 175-185℃, and feeding the granules into the extruder for extrusion molding to obtain pulp / polyethylene composite material.